Potential Benefits of Limited Clinical and Radiographic Follow-up After Surgical Treatment of Ankle Fractures. (May 2021) - Friedman, Lisa G. M.; Sanchez, Daniela; Zachos, Terri A.; Marcantonio, Andrew; Audet, Megan; Vallier, Heather; Mullis, Brian; Myers-White, Adam; Kempton, Laurence; Watts, Jeffrey; Horwitz, Daniel S.
Abstract : Introduction: Ankle fractures are one of the most prevalent musculoskeletal injuries, with a significant number requiring surgical treatment. Postoperative complications requiring additional interventions frequently occur during the early postoperative period. We hypothesize that there is a limited need for routine clinical and radiographic follow-up once the fracture is deemed healed. Methods: IRB approval was obtained at four academic trauma centers. A retrospective chart review was done to identify adults with healed unimalleolar and bimalleolar ankle fractures treated surgically with at least 12 months of follow-up. Based on postoperative radiographs, changes in fracture alignment and implant position from radiographic union to final follow-up were documented. The average reimbursement for a final follow-up clinic visit and a set of ankle radiographs were estimated. Results: A total of 140 patients met inclusion criteria. The mean age at injury was 49.5 years, and 67.9% of patients were female. The mean time to healing was 82.2 days (±33.5 days). After radiographic healing, one patient had radiographic changes but was asymptomatic and full weight bearing at their final follow-up. On average, our institution was reimbursed 46 to 49 for a follow-up clinic visit and 364 to 497 for a set of ankle radiographs. Conclusion: Given the average time to healing, there is limited utility in routine radiographic and clinical follow-up beyond 16 weeks in asymptomatic patients. In our series, this would result in a savings of 950 to 1, 200 per patient. However, after ankle fractures were deemed healed, 0.7% patients had radiographic evidence of a change in implant position. Documenting this change did not modify the immediate course of fracture treatment. Surgeons will need to balance the need for routine follow-up with the potential economic benefits in reducing costs to the healthcare system.